Lightweight modified plastic and preparation method thereof

Through plasma surface treatment and supercritical micropore injection molding technology, hollow glass microbeads are modified and combined with xanthan gum and ABS high glue powder to form a foam skeleton structure, solving the problem of deterioration of toughness caused by the rigidity and brittleness of hollow glass microbeads. It realizes the lightweight and high toughness of plastics, suitable for high-end electronic products and transportation.

CN119192769AInactive Publication Date: 2024-12-27QINGDAO ZHONGBAO PLASTIC IND CO LTD

Patent Information

Application Number
CN202411470423.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing plastic lightweight modification technology, the rigidity and brittleness of hollow glass microbeads lead to a decrease in toughness of the finished product, making it difficult to apply in fields that require falling and impact resistance. At the same time, the high density of hollow glass microbeads limit the lightness of the plastic. Quantitative effect.

Method used

Fluorocarbon groups are introduced through plasma surface treatment technology, hollow glass microbeads are modified, combined with xanthan gum and ABS high glue powder as toughening agents, and supercritical micropore injection molding technology is used to form a foam skeleton structure to improve the toughness of the plastic and impact resistance.

Benefits of technology

It significantly improves the toughness and impact resistance of plastics, and at the same time realizes the lightweighting of plastics, reducing the density to 0.84-0.88g/cm3, meeting the lightweighting needs of high-end electronic products and transportation tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094537310000061
    Figure BDA0005094537310000061
  • Figure BDA0005094537310000081
    Figure BDA0005094537310000081
  • Figure BDA0005094537310000091
    Figure BDA0005094537310000091
Patent Text Reader

Abstract

The invention relates to the technical field of plastic processing, and particularly discloses lightweight modified plastic and a preparation method thereof. The light-weight modified plastic is prepared from the following raw materials in parts by weight: 45 to 60 parts of polycarbonate, 45 to 60 parts of acrylonitrile-butadiene-styrene resin, 30 to 40 parts of fluorinated hollow glass beads, 6 to 11 parts of a toughening agent, 1 to 3 parts of a compatilizer, 0.4 to 1.2 parts of a coupling agent and 0.1 to 0.5 part of an antioxidant. Raw materials of the fluorinated hollow glass beads comprise hollow glass beads and chlorotrifluoroethylene. According to the lightweight modified plastic disclosed by the invention, the phenomena that the toughness of a finished product is reduced and the finished product is not resistant to impact due to the rigidity and brittleness of the hollow glass beads are effectively improved, and the modified plastic has excellent toughness and impact resistance while the lightweight of the plastic is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of plastic processing, and more specifically, to a lightweight modified plastic and a preparation method thereof. Background Art

[0002] With the rapid development of global science and technology and the improvement of people's living standards, the lightweighting of electronic products and vehicles has become an important trend in the development of the industry. Lightweighting not only helps to improve the portability and comfort of products, but also significantly improves energy efficiency, reduces energy consumption and emissions, and meets the current requirements of green environmental protection and sustainable development.

[0003] As the main material for electronic products and vehicle shells, decorations and structural parts, plastic lightweight modification technology is particularly important, especially for areas that need to strictly control the overall weight, such as high-end smart phones, tablets, new energy vehicles, etc., the demand for lightweight modification of plastics is more urgent.

[0004] Because hollow glass microspheres have a unique hollow structure, they can significantly reduce the density of the material while maintaining the strength of the material. They have become an effective means of lightweighting plastics and have achieved weight reduction for PC / ABS plastics to a certain extent.

[0005] With regard to the above-mentioned related technologies, the inventors found that due to the rigidity and brittleness of the hollow glass microspheres themselves, the toughness of the final product is easily reduced, and it is not resistant to impact, making it difficult to be used in some fields that require high resistance to falling (such as mobile phone housings) and impact (such as automotive structural parts). In addition, the hollow glass microspheres that can be used in plastic extrusion and injection molding processes have a high density. For example, the density of injection-molding-grade hollow glass microspheres is generally 200-700kg / m 3 Due to the limitation of process, the amount of addition is not high, resulting in poor lightweight effect of the final product, and the density of the finished product is difficult to be lower than 900kg / m 3 . Summary of the invention

[0006] In order to reduce the density of plastics and improve the toughness of plastics, the present application provides a lightweight modified plastic and a preparation method thereof.

[0007] In a first aspect, the present application provides a lightweight modified plastic, which adopts the following technical solution: A lightweight modified plastic, wherein the raw materials include 45-60 parts of polycarbonate, 45-60 parts of acrylonitrile-butadiene-styrene resin, 30-40 parts of fluorinated hollow glass microspheres, 6-11 parts of toughening agent, 1-3 parts of compatibilizer, 0.4-1.2 parts of coupling agent and 0.1-0.5 parts of antioxidant in parts by weight; the raw materials of the fluorinated hollow glass microspheres include hollow glass microspheres and chlorotrifluoroethylene.

[0008] By adopting the above technical solution, the hollow glass microspheres have a cavity structure inside, and as fillers, they can effectively reduce the weight of plastics and achieve lightweighting of plastics.

[0009] By modifying the hollow glass microspheres with chlorotrifluoroethylene, fluorocarbon groups can be introduced on the surface of the hollow glass microspheres through surface treatment.

[0010] On the one hand, the introduction of fluorine-containing groups significantly reduces the surface energy of hollow glass microspheres, improves the lubricity of hollow glass microspheres in the plastic matrix, significantly reduces the aggregation tendency between hollow glass microspheres, and forms a more stable network structure in the plastic matrix. The improvement of lubricity effectively reduces the resistance of energy transfer inside the plastic matrix, so that the finished product can effectively absorb and disperse energy when impacted. At the same time, by modifying the lubricity of the surface of hollow glass microspheres, it can replace lubricants and compatibilizers, promote the compatibility between the plastic matrix and other raw materials, further reduce the density of modified plastics, and promote the lightweighting of plastics.

[0011] On the other hand, due to the strong electronegativity of fluorine atoms, the fluorocarbon group has a high chemical stability. This stability enables the fluorocarbon group to maintain its structural integrity when facing external energy impact and is not prone to chemical changes. It strengthens the hollow structure of the hollow glass microspheres to absorb and disperse energy when impacted, and effectively overcomes the problem of reduced toughness and impact resistance of the finished product due to the rigidity and brittleness of the hollow glass microspheres themselves, so that the modified plastic has excellent toughness and impact resistance.

[0012] Optionally, the method for preparing the fluorinated hollow glass microspheres comprises the following steps: S1: placing the hollow glass microspheres in a plasma reaction chamber for plasma treatment, setting the system vacuum degree to 10-25 Pa, the processing power to 110-120 W, the processing frequency to 10-12 kHz, and introducing a mixed gas for surface activation modification for 3-5 min; S2: In the plasma environment, chlorotrifluoroethylene gas was introduced into the reaction chamber for plasma polymerization for 20-25 min. The deposition amount of hollow glass microspheres per unit area was 8.25-8.75×10 -3 g / mm 2 .

[0013] By adopting the above technical scheme, the plasma surface treatment technology generates high-energy particles through ionized gas. These particles can penetrate into the micropores and pits of the hollow glass microspheres, effectively activate the surface of the hollow glass microspheres, increase the surface reaction active points, provide good grafting conditions for the grafting of trifluorochloroethylene, and effectively give the hollow glass microspheres good surface properties.

[0014] Optionally, the mixed gas is argon and hydrogen with a flow ratio of 1:(2.5-3.5), and the flow rate of the mixed gas is 0.24-0.36 L / min.

[0015] By adopting the above technical solution, hydrogen is a highly reactive gas, and when mixed with more inert argon, the reaction activity in the plasma can be increased, thereby promoting the plasma surface modification reaction of the hollow glass microspheres.

[0016] Optionally, the toughening agent is xanthan gum and ABS high rubber powder in a mass ratio of 1:(3-5).

[0017] By adopting the above technical solution, ABS high-rubber powder, with its high rubber content, significantly enhances the toughness and impact resistance of the material, making the product have better resistance when subjected to external forces. Xanthan gum, with its unique rheology and thickening ability, plays the role of stabilizer in the mixed system, further consolidating the toughening effect. The synergistic use of the two helps to promote the easy processing of the mixture and effectively improves the stability and durability of the modified plastic.

[0018] Optionally, the coupling agent is any one of a silane coupling agent or a titanate coupling agent.

[0019] By adopting the above technical solution, the silane coupling agent and the titanate coupling agent can play a bridging role in the modified plastic, enhance the interfacial bonding force between the hollow glass microspheres and the matrix resin, and thus improve the mechanical properties and toughness of the plastic.

[0020] Optionally, the compatibilizer is any one of maleic anhydride or polypropylene grafted with maleic anhydride.

[0021] By adopting the above technical solution, maleic anhydride or polypropylene grafted maleic anhydride as a compatibilizer can improve the compatibility between different resins and raw material components, reduce phase separation, and improve the uniformity and toughness of plastics.

[0022] Optionally, the antioxidant is any one or more combinations of antioxidant B215, antioxidant 1010, antioxidant 1076 and antioxidant B225.

[0023] By adopting the above technical solution, the antioxidant can prevent the plastic from oxidative degradation during processing and use, thereby maintaining the mechanical properties and toughness of the plastic.

[0024] In a second aspect, the present application provides a method for preparing a lightweight modified plastic, using the following technical solution: A method for preparing a lightweight modified plastic comprises the following steps: S1: mixing polycarbonate and acrylonitrile-butadiene-styrene resin to form a premix A; S2: uniformly mixing the fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant to obtain a premix B; S3: adding the premix A from the main feeding port of the single screw extruder, and adding the premix B from the side feeding port of the single screw extruder, and obtaining blended particles after extrusion and granulation; S4: Put the blended particles into the barrel of the supercritical microporous injection molding equipment, inject supercritical fluid carbon dioxide with a mass of 0.5-1.2% of the mass of the blended particles, set the barrel temperature to 220-250°C, and the holding pressure to 10-15MPa, form a homogeneous system with the blended particles under the shearing action of the injection molding machine screw, and perform micro-foaming injection molding to obtain.

[0025] By adopting the above technical scheme, supercritical carbon dioxide is used as the foam phase for micro-foaming to form a foam phase, thereby forming a three-phase foam skeleton structure with polycarbonate (PC) and acrylonitrile-butadiene-styrene resin (ABS) as the matrix phase, fluorinated hollow glass microspheres as the reinforcement phase, and supercritical carbon dioxide as the foam phase.

[0026] The cellular structure formed by supercritical carbon dioxide foaming can provide additional support points for plastics, limit the expansion path of cracks, and thus delay the destruction of the material. When impacted, the foam skeleton structure can effectively absorb and disperse energy, reduce material damage, and significantly improve the toughness and impact resistance of the material.

[0027] Optionally, the barrel temperature of the single screw extruder is 220-250° C., and the screw speed is 200-300 rpm.

[0028] In summary, this application has the following beneficial effects: 1. The present application modifies the surface of hollow glass microspheres by plasma surface treatment technology, introduces fluorocarbon groups, significantly improves the lubricity of hollow glass microspheres in plastic matrix, reduces the resistance of internal energy transfer of plastic when impacted, and at the same time, the introduction of fluorine-containing groups significantly improves the ability of hollow glass microspheres to resist deformation and breakage by external forces, effectively improving the phenomenon that the toughness of finished products decreases and they are not resistant to impact due to the rigidity and brittleness of the hollow glass microspheres themselves.

[0029] 2. This application uses a mixture of xanthan gum and ABS high-rubber powder as a toughening agent, which effectively combines the rheological and thickening ability of xanthan gum and the toughening and easy processing properties of ABS high-rubber powder, effectively improving the resistance of the modified plastic to external forces.

[0030] 3. The method of the present application introduces a micro-foam structure as a foam phase through supercritical microporous injection molding technology, forming a three-phase foam skeleton structure with polycarbonate (PC) and acrylonitrile-butadiene-styrene resin (ABS) as a matrix phase, fluorinated hollow glass microspheres as a reinforcement phase, and supercritical carbon dioxide as a foam phase, thereby further achieving lightweight of the modified plastic and ensuring that the modified plastic has excellent toughness and impact resistance. DETAILED DESCRIPTION

[0031] The following examples further illustrate the present application in detail.

[0032] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Polycarbonate, selected from Lerui Plastics, CHXN120C; Acrylonitrile-butadiene-styrene resin, selected from Inno Plastics, YN821; Hollow glass microspheres, selected from Weizhen New Materials, hollow glass microspheres 5022, effective density 0.25g / cm 3 , particle size distribution is 10-110μm; Chlorotrifluoroethylene, selected from Huibao Chemical, purity 99.9%, CAS: 79-38-9; Xanthan gum, selected from Shanghai Yuanye Biotechnology, S30551; ABS high glue powder, selected from Korea Kumho, POWHR150; Silane coupling agent, methyltrimethoxysilane, selected from Shandong sodium magnesium new materials, kh-560; Titanate coupling agent, isopropyl tri(dioctylphosphoyloxy)titanate, selected from Lanzhu, 201; Maleic anhydride, selected from Qixiang Tengda, 036; Polypropylene grafted with maleic anhydride, selected from Exxon, PO1015; Pentaerythritol stearate, selected from Dingxin plastic raw materials, DX-R01.

[0033] Preparation Example of Fluoride Glass Microspheres Preparation Example 1 The preparation method of fluoride glass microspheres comprises the following steps: S1: Place the hollow glass microspheres in a plasma reaction chamber for plasma treatment, set the system vacuum degree to 12Pa, the processing power to 120W, the processing frequency to 12kHz, introduce a mixed gas of argon and hydrogen with a flow ratio of 1:2.5 for surface activation modification for 3min, and the flow rate of the mixed gas is 0.24L / min; S2: In the plasma environment, chlorotrifluoroethylene gas was introduced into the reaction chamber and plasma polymerization was carried out for 25 min. The deposition amount of hollow glass microspheres per unit area was 8.25×10 -3 g / mm 2 .

[0034] Preparation Example 2 The preparation method of fluoride glass microspheres comprises the following steps: S1: Place the hollow glass microspheres in a plasma reaction chamber for plasma treatment, set the system vacuum degree to 17Pa, the processing power to 110W, the processing frequency to 10kHz, introduce a mixed gas of argon and hydrogen with a flow ratio of 1:3.5 for surface activation modification for 5min, and the flow rate of the mixed gas is 0.3L / min; S2: In the plasma environment, chlorotrifluoroethylene gas was introduced into the reaction chamber and plasma polymerization was carried out for 20 min. The deposition amount per unit area of ​​hollow glass microspheres was 8.47×10 -3 g / mm 2 .

[0035] Preparation Example 3 The preparation method of fluoride glass microspheres comprises the following steps: S1: Place the hollow glass microspheres in a plasma reaction chamber for plasma treatment, set the system vacuum degree to 25Pa, the processing power to 115W, the processing frequency to 11kHz, introduce a mixed gas of argon and hydrogen with a flow ratio of 1:3 for surface activation modification for 5min, and the flow rate of the mixed gas is 0.36L / min; S2: In the plasma environment, chlorotrifluoroethylene gas was introduced into the reaction chamber and plasma polymerization was carried out for 25 min. The deposition amount of hollow glass microspheres per unit area was 8.75×10 -3 g / mm 2 .

[0036] Preparation Example 4 The preparation method of fluorinated glass microspheres is different from that of Preparation Example 1 in that an equal flow rate of argon gas is introduced in step S1, and the other steps are the same as those of Preparation Example 1.

[0037] Preparation Example 5 The preparation method of fluorinated glass microspheres is different from that of Preparation Example 1 in that an equal flow rate of hydrogen is introduced in step S1, and the other steps are the same as those of Preparation Example 1. Example

[0038] Example 1 A lightweight modified plastic, wherein the raw materials and amounts are shown in Table 1, wherein the fluorinated hollow glass microspheres are obtained by Preparation Example 1, the toughening agent is xanthan gum and ABS high rubber powder in a mass ratio of 1:3, the compatibilizer is maleic anhydride, the coupling agent is a silane coupling agent, and the antioxidant is antioxidant B215.

[0039] Table 1 The above-mentioned method for preparing a lightweight modified plastic comprises the following steps: S1: uniformly mixing polycarbonate and acrylonitrile-butadiene-styrene resin to obtain a premix A; S2: adding fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant into a high-speed mixer, stirring at 1000 rpm for 3 min, and then stirring at 2000 rpm for 5 min to obtain premix B; S3: adding premix A from the main feeding port of the single-screw extruder, feeding premix B from the side feeding port, and obtaining blended particles after extrusion and granulation; setting the barrel temperature range of the single-screw extruder to 220-250° C., and the screw speed to 200-300 rpm; S4: putting the blended particles into the barrel of a supercritical microporous injection molding equipment, injecting supercritical fluid carbon dioxide with a mass of 0.8% of the mass of the blended particles as a foaming gas, setting the barrel temperature to 220-250° C., and the holding pressure to 12 MPa, forming a homogeneous system with the blended particles under the shearing action of the injection molding machine screw, and performing micro-foaming injection molding to obtain.

[0040] Example 2 A lightweight modified plastic, which is different from Example 1 in that the raw materials and amounts are shown in Table 1, wherein the fluorinated hollow glass microspheres are obtained from Preparation Example 2, the toughening agent is xanthan gum and ABS high-rubber powder in a mass ratio of 1:4, the compatibilizer is polypropylene grafted maleic anhydride, the coupling agent is a titanate coupling agent, and the antioxidant is antioxidant 1010; The above-mentioned method for preparing a lightweight modified plastic comprises the following steps: S1: uniformly mixing polycarbonate and acrylonitrile-butadiene-styrene resin to obtain a premix A; S2: adding fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant into a high-speed mixer, stirring at 1000 rpm for 3 min, and then stirring at 2000 rpm for 5 min to obtain premix B; S3: adding premix A from the main feeding port of the single-screw extruder, and feeding premix B from the side feeding port, and obtaining blended particles after extrusion and granulation; setting the barrel temperature range of the single-screw extruder to 220-250° C., and the screw speed to 200-300 rpm; S4: putting the blended particles into the barrel of a supercritical microporous injection molding equipment, injecting supercritical fluid carbon dioxide with a mass of 1.2% of the mass of the blended particles as a foaming gas, setting the barrel temperature to 220-250° C., and the holding pressure to 10 MPa, forming a homogeneous system with the blended particles under the shearing action of the injection molding machine screw, and performing micro-foaming injection molding to obtain.

[0041] Example 3 A lightweight modified plastic, which is different from Example 1 in that the raw materials and amounts are as shown in Table 1, wherein the fluorinated hollow glass microspheres are obtained from Preparation Example 3, the toughening agent is xanthan gum and ABS high rubber powder in a mass ratio of 1:5, and the antioxidant is antioxidant 1076; The above-mentioned method for preparing a lightweight modified plastic comprises the following steps: S1: uniformly mixing polycarbonate and acrylonitrile-butadiene-styrene resin to obtain a premix A; S2: adding fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant into a high-speed mixer, stirring at 1000 rpm for 3 min, and then stirring at 2000 rpm for 5 min to obtain premix B; S3: adding premix A from the main feeding port of the single-screw extruder, and feeding premix B from the side feeding port, and obtaining blended particles after extrusion and granulation; setting the barrel temperature range of the single-screw extruder to 220-250° C., and the screw speed to 200-300 rpm; S4: putting the blended particles into the barrel of a supercritical microporous injection molding equipment, injecting supercritical fluid carbon dioxide with a mass of 1.2% of the mass of the blended particles as a foaming gas, setting the barrel temperature to 220-250° C., and the holding pressure to 15 MPa, forming a homogeneous system with the blended particles under the shearing action of the injection molding machine screw, and performing micro-foaming injection molding to obtain.

[0042] Example 4 A lightweight modified plastic, which is different from Example 1 in that the raw materials and amounts are as shown in Table 1, the antioxidant is antioxidant B225, and the other steps are the same as Example 1.

[0043] Example 5 A lightweight modified plastic, which differs from Example 1 in that ABS high-rubber powder is not added, the toughening agent is xanthan gum, and the other steps are the same as those of Example 1.

[0044] Example 6 A lightweight modified plastic, which differs from Example 1 in that xanthan gum is not added, the toughening agent is ABS high-rubber powder, and the other steps are the same as those of Example 1.

[0045] Example 7 A lightweight modified plastic, which is different from Example 1 in that the fluorinated hollow glass microspheres are obtained by Preparation Example 4, and the other steps are the same as those of Example 1.

[0046] Example 8 A lightweight modified plastic, which is different from Example 1 in that the fluorinated hollow glass microspheres are obtained by Preparation Example 5, and the other steps are the same as those of Example 1.

[0047] Comparative Example Comparative Example 1 A lightweight modified plastic, which differs from Example 1 in that fluorinated hollow glass microspheres are not used, the hollow glass microspheres in the raw material are replaced by polycarbonate of equal mass, and the other steps are the same as those of Example 1.

[0048] Comparative Example 2 A lightweight modified plastic, which differs from Example 1 in that the fluorinated hollow glass microspheres in the raw material are replaced by hollow glass microspheres that have not been plasma surface treated, and the other steps are the same as Example 1.

[0049] Comparative Example 3 A lightweight modified plastic, which differs from Example 1 in that the fluorinated hollow glass microspheres in the raw materials are replaced by hollow glass microspheres that have not been plasma surface treated, 2 g of the hollow glass microspheres are replaced by a lubricant of equal mass, and are mixed with other raw materials in step S2 to form a premix B, the lubricant is pentaerythritol stearate, and the other steps are the same as in Example 1.

[0050] Comparative Example 4 A lightweight modified plastic, which is different from Example 1 in that its preparation method comprises the following steps: S1: uniformly mixing polycarbonate and acrylonitrile-butadiene-styrene resin to obtain a premix A; S2: adding fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant into a high-speed mixer, stirring at 1000 rpm for 3 min, and then stirring at 2000 rpm for 5 min to obtain premix B; S3: premix A is added from the main feeding port of the single screw extruder, and premix B is fed from the side feeding port. The barrel temperature of the single screw extruder is set to 220-250° C., and the screw speed is set to 200-300 rpm. The product is obtained after extrusion, granulation and drying.

[0051] Performance testing The lightweight modified plastics obtained in Examples 1-8 and Comparative Examples 1-4 were subjected to performance testing tests of density, tensile strength, notched impact strength and elastic modulus.

[0052] Density: Tested in accordance with ISO 1183-1-2019 standard; Tensile strength: Tested according to IS0 527, test condition 50mm / min; Elastic modulus: refer to ISO 178, test conditions are 2mm / min, 64mm; Notched impact strength: Refer to ISO 179, test condition is 23℃.

[0053] Table 2 According to the performance test results in Table 2, it can be seen that the density range of a lightweight modified plastic in the present application is 0.84-0.88 g / cm 3 , notched impact strength range 49.4-50.7kJ / m 2 This shows that filling plastics with hollow glass microspheres can effectively achieve plastic lightweighting. By modifying the hollow glass microspheres, it is possible to further achieve plastic lightweighting while effectively improving the phenomenon of reduced toughness and impact resistance of the finished product due to the rigidity and brittleness of the hollow glass microspheres themselves, so that the modified plastics have excellent toughness and impact resistance.

[0054] According to the performance test results of Examples 1-4 and Comparative Examples 1-3, it can be seen that filling plastics with hollow glass microspheres can effectively achieve lightweight plastics. Modifying the surface of hollow glass microspheres by plasma surface treatment to introduce fluorocarbon groups can replace traditional plastic lubricants, further achieving lightweight plastics while significantly improving the dispersibility of hollow glass microspheres in the plastic matrix.

[0055] The spherical structure and improved lubricity of the hollow glass microspheres enable them to roll in the plastic matrix like a ball bearing, reducing the viscosity and internal stress of the resin mixture and the resistance to internal energy transfer when the plastic is impacted. At the same time, the introduction of fluorine-containing groups significantly enhances the ability of the hollow glass microspheres to resist deformation and breakage due to external forces.

[0056] It can be seen from the performance test results of Examples 1-4 and Comparative Example 4 that the micro-foam structure is introduced as the foam phase through the supercritical microporous injection molding technology to form a three-phase foam skeleton structure, which can further achieve the lightweight of the modified plastic. At the same time, when impacted, the foam skeleton structure can effectively absorb and disperse energy, reduce material damage, and ensure that the modified plastic has excellent toughness and impact resistance.

[0057] According to the performance test results of Examples 1-4 and 5-6, it can be seen that the mixture of xanthan gum and ABS high rubber powder as a toughening agent effectively combines the rheological and thickening ability of xanthan gum and the toughening and easy processing performance of ABS high rubber powder. Compared with the use of a single toughening agent, it effectively improves the resistance of the modified plastic to external forces.

[0058] It can be seen from the performance test results of Examples 1-4 and Examples 7-8 that hydrogen is a highly reactive gas. When mixed with more inert argon, it can increase the reactivity in the plasma, thereby promoting the plasma surface modification reaction of the hollow glass microspheres and improving the toughness and impact resistance of the final product.

[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lightweight modified plastic, characterized in that: The raw materials include 45-60 parts of polycarbonate, 45-60 parts of acrylonitrile-butadiene-styrene resin, 30-40 parts of fluorinated hollow glass microspheres, 6-11 parts of toughening agent, 1-3 parts of compatibilizer, 0.4-1.2 parts of coupling agent and 0.1-0.5 parts of antioxidant in parts by weight; the raw materials of the fluorinated hollow glass microspheres include hollow glass microspheres and chlorotrifluoroethylene.

2. The lightweight modified plastic according to claim 1, characterized in that: The method for preparing the fluorinated hollow glass microspheres comprises the following steps: S1: placing the hollow glass microspheres in a plasma reaction chamber for plasma treatment, setting the system vacuum degree to 10-25 Pa, the processing power to 110-120 W, the processing frequency to 10-12 kHz, and introducing a mixed gas for surface activation modification for 3-5 min; S2: In the plasma environment, chlorotrifluoroethylene gas was introduced into the reaction chamber for plasma polymerization for 20-25 min. The deposition amount of hollow glass microspheres per unit area was 8.25-8.75×10 -3 g / mm 2 .

3. The lightweight modified plastic according to claim 2, characterized in that: The mixed gas is argon and hydrogen with a flow ratio of 1:(2.5-3.5), and the flow rate of the mixed gas is 0.24-0.36 L / min.

4. The lightweight modified plastic according to claim 1, characterized in that: The toughening agent is xanthan gum and ABS high rubber powder in a mass ratio of 1:(3-5).

5. The lightweight modified plastic according to claim 1, characterized in that: The coupling agent is any one of a silane coupling agent or a titanate coupling agent.

6. The lightweight modified plastic according to claim 1, characterized in that: The compatibilizer is any one of maleic anhydride or polypropylene grafted with maleic anhydride.

7. The lightweight modified plastic according to claim 1, characterized in that: The antioxidant is any one or more combinations of antioxidant B215, antioxidant 1010, antioxidant 1076 and antioxidant B225.

8. A method for preparing a lightweight modified plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: mixing polycarbonate and acrylonitrile-butadiene-styrene resin to form a premix A; S2: uniformly mixing the fluorinated hollow glass microspheres, toughening agent, compatibilizer, coupling agent and antioxidant to obtain a premix B; S3: adding the premix A from the main feeding port of the single screw extruder, and adding the premix B from the side feeding port of the single screw extruder, and obtaining blended particles after extrusion and granulation; S4: Put the blended particles into the barrel of the supercritical microporous injection molding equipment, inject supercritical fluid carbon dioxide with a mass of 0.5-1.2% of the mass of the blended particles, set the barrel temperature to 220-250°C, and the holding pressure to 10-15MPa, form a homogeneous system with the blended particles under the shearing action of the injection molding machine screw, and perform micro-foaming injection molding to obtain.

9. The method for preparing a lightweight modified plastic according to claim 8, characterized in that: The barrel temperature of the single screw extruder is 220-250°C and the screw speed is 200-300rpm.

Citation Information

Patent Citations

  • Fluorine-containing polymer functionalized carbon nanotube and preparation method thereof

    CN103241724A

  • Hollow glass bead modification method and application thereof

    CN106830667A

  • Modified talcum powder for transparent plastic filling and preparation method thereof

    CN108659577A

  • Lightweight PC / ABS weight loss composite material and preparation method thereof

    CN109096725A

  • Environment-friendly regenerated PET modified PC / ABS alloy and preparation method thereof

    CN115895225A

Cited By

  • Lightweight impact-resistant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) and application thereof in robot shell

    CN120865690A